Investigating the Effects of All-trans Retinoic Acid on Histopathology of Pancreas of streptozotocin -Induced Diabetes in C57BL/6 mice - Farin Malekifard; Nowruz Delirezh; Rahim Hobbnaghi; Hasan Malekinejad (Fasa University of Medical Sciences, 2018)
Backgrounds & Objectives: Type 1 diabetes is an auto-immune disease and caused by insufficient insulin production by the body. All-trans Retinoic Acid (ATRA) is an antioxidant, anti-cancer and anti-inflammatory agent. The objective of the present study was to investigate the effects of ATRA on histopathology of pancreas in diabetic mice. Material & Methods: Diabetes was induced by multiple low-dose of streptozotocin injection (40 mg/kg/day for 5 consecutive days) in male C57BL/6 mice. After induction of diabetes, mice were treated with ATRA (20 mg/kg/day i.p.) for 21 days. On the last day, pancreases were isolated and stained with hematoxylin &eosin (H&E) and Gomeri aldehyde fuchsin (GAF) for histological analyses (the number of islets and β cells, diameter of islets) of pancreas. Results: ATRA treatment in streptozotocin-induced diabetic mice was increased the mean diameter of islets and the number of islets and beta cells compared to the diabetic group. (p<0/05). Conclusion: The administration of ATRA improved pancreas tissue during destruction of the pancreatic beta-cells in STZ-induced type 1 diabetes in mice.